Effective Dose of Rosella Calyx Extract (Hibiscus sabdariffa L.) against Liver Marker Enzymes and Liver Histopathological of High-Fat Feed-Induced Rats - Hidayat, Meilinah; Adhika, Oeij A; Tanuwijaya, Fenny; Nugraha, Adisurya; Hutagalung, Ricky B (Journal of Medicine and Health, 2019)
Liver disease is a disease caused by various factors that damage the liver, such as viruses, obesity and alcohol consumption. Many studies have been done to find natural remedies for this disease, one of which is Rosella. In this research, the effective dose of ethanol extract of rosella calyx (EERC) was conducted, in high-fat feed (HFF)-induced rats. The aim of this study was to determine the effective dose of EEKR based on parameters:liver histopathological, Alanine Transferase (ALT) and Gamma Glutamyl Transferase (GGT) level. The study was conducted on 30 male Wistar rats, which were divided into five treatment groups. As results, histopathological observations showed a significant decrease in cloudy swelling scores at EERC 200 mg/KgBW/d, decreased steatosis scores at doses of 200, 400, 600 mg; whereas ballooning degeneration, lobular inflammation, and fibrosis scores did not decrease. EERC 200, 400, 600 mg/KgBW/d significantly decreased ALT (p ? 0.01); while doses of 400 and 600 mg reduce GGT. Conclusions, effective dose of EEKR for liver disease based on histopathological features of liver, ALT and GGT in HFF- induced Wistar rats is dose of 200 - 400 mg /KgBW/day. Keywords: effective dose, Rosella, histopathologic, Alanine Transferase, Gamma Glutamyl Transferase